An Integrated Analysis of Shut-In Well Reactivation for Oil Production Optimization in The DLN-11 Well - Yusgiantoro, Luky Agung; Hariyadi; Paradhita, Windyanesha; Kristanto, Dedi (Scientific Contributions Oil and Gas, 2026)
DLN-11 well was temporarily shut-in due to excessive water production, which became the main issue causing a decline in daily oil production. Therefore, this study conducted an integrated analysis to determine the cause of excessive water production, so that appropriate mitigation measures could be implemented, as well as to formulate a well reactivation strategy aimed at optimizing oil production. The methodology in this study was carried out in an integrated manner through technical and economic evaluations. The technical analysis began with the application of the Chan diagnostic plot as an initial mitigation step, followed by the evaluation of data logging, core analysis data, and production data as advanced mitigation steps to obtain appropriate solutions for addressing production-related issues. In addition, an economic analysis was conducted as a basis for decision-making within a risk management framework. Based on the results of the integrated analysis between the Chan diagnostic plot method and cement evaluation data from Cement Bond Log (CBL), Variable Density Log (VDL) dan Ultra Sonic Imaging Tool (USIT), the high water cut in DLN-11 well, as a reactivation candidate, was caused by water channeling due to the presence of free pipe conditions, where the cement did not properly isolate the annulus between the casing and the formation. To overcome this issue, remedial cementing was carried out to improve the quality of cement bonding. Furthermore, based on the evaluation results of the C/O Log, DLN-11 well still owns five potential oil-bearing zones that can be produced. The reactivation strategy was implemented by opening the interval of 7927-7942 ftMD, resulting in a production rate of 549 BOPD with a water cut of 82%. The economic analysis results indicate that DLN-11 well yields an NPV of 1,256,000 US$, an IRR of 247.5%, and a Pay Out Time (POT) of 3 months and 16 days. Therefore, from both technical and economic perspectives, the implemented reactivation strategy for DLN-11 well has proven to increase oil production and generate positive economic indicators.